Accelerated triacylglycerol production and altered fatty acid composition in oleaginous microalga Neochloris oleoabundans by overexpression of diacylglycerol acyltransferase 2 - Klaitong, Paeka (Microb Cell Fact, 2017)
BACKGROUND: Microalgae are promising sources of lipid triacylglycerol (TAG) for biodiesel production. However, to date, microalgal biodiesel is technically feasible, but not yet economically viable. Increasing TAG content and productivity are important to achieve economic viability of microalgal biodiesel. To increase TAG content, oleaginous microalga Neochloris oleoabundans was genetically engineered with an endogenous key enzyme diacylglycerol acyltransferase 2 (NeoDGAT2) responsible for TAG biosynthesis. RESULTS: The integration of NeoDGAT2 expression cassettes in N. oleoabundans transformant was confirmed by PCR. The neutral lipid accumulation in the transformant detected by Nile red staining was accelerated and 1.9-fold higher than in wild type; the lipid bodies in the transformant visualized under fluorescence microscope were also larger. The NeoDGAT2 transcript was two-fold higher in the transformant than wild type. Remarkably higher lipid accumulation was found in the transformant than wild type: total lipid content increased 1.6-to 2.3-fold up to 74.5 ± 4.0% dry cell weight (DCW) and total lipid productivity increased 1.6- to 3.2-fold up to 14.6 ± 2.0 mg/L/day; while TAG content increased 1.8- to 3.2-fold up to 46.1 ± 1.6% DCW and TAG productivity increased 1.6- to 4.3-fold up to 8.9 ± 1.3 mg/L/day. A significantly altered fatty acid composition was detected in the transformant compared to wild type; the levels of saturated fatty acid C16:0 increased double to 49%, whereas C18:0 was reduced triple to 6%. Long-term stability was observed in the transformant continuously maintained in solid medium over 100 generations in a period of about 4 years. CONCLUSIONS: Our results demonstrate the increased TAG content and productivity in N. oleoabundans by NeoDGAT2 overexpression that may offer the first step towards making microalgae an economically feasible source for biodiesel production. The strategy for genetically improved microalga presented in this study can be applied to other microalgal species possessing desired characteristics for industrial biofuel production.